Globalisation and the quest for social and environmental justice (Abingdon, Oxon [UK] ; New York)
1 online resource (xiii, 304 pages)
Keywords: There are few topics as controversial as globalisation. It is meant to bring economic growth and solve a range of social, cultural and humanitarian problems. However, there are significant debates in relation to the extent that the reality of globalisation reflects this idealized vision. In particular, globalisation has produced a highly interdependent world, rendering state boundaries meaningless and challenging the ideology and limits of certain areas of international law. This book will provide the opportunity to address some of the multifaceted issues provoked by the issue of globalisation. The book is an exploration of the intricate nexus that emerges as a result of globalisation, inextricably linking together issues of international law, human rights, environmental law and international trade law. Bringing together a number of experts in the field, the book focuses on the areas of social justice and environmental justice, and explores the links that exists between the two and the effect of globalisation on these areas.